2005
DOI: 10.1111/j.1460-2695.2005.00854.x
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic two‐scale model for high‐cycle fatigue life predictions

Abstract: It is proposed to develop and identify a probabilistic two-scale model for HCF that accounts for the failure of samples but also for the thermal effects during cyclic loadings in a unified framework.The probabilistic model is based on a Poisson point process. Within the weakest link theory, the model corresponds to a Weibull law for the fatigue limits. The thermal effects can be described if one considers the same hypotheses apart from the weakest link assumption. A method of identification is proposed and use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
152
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(156 citation statements)
references
References 30 publications
1
152
0
3
Order By: Relevance
“…For this type of mechanism, it was shown that the power law (1) is able to model not only the fatigue properties but also dissipation phenomena [23]. As explained in Section 2.3, continuous formation of mesocracks corresponds to an incubation "time" (or number of cycles), that is the time needed by microcracks to initiate and propagate before forming a mesocrack.…”
Section: Microcrack Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…For this type of mechanism, it was shown that the power law (1) is able to model not only the fatigue properties but also dissipation phenomena [23]. As explained in Section 2.3, continuous formation of mesocracks corresponds to an incubation "time" (or number of cycles), that is the time needed by microcracks to initiate and propagate before forming a mesocrack.…”
Section: Microcrack Densitymentioning
confidence: 99%
“…This hypothesis was already used to analyze probabilistic features associated with brittle fracture [18], multiple cracking of composites [19], dynamic fragmentation of ceramics [20], damage and fracture in cyclic fatigue [21][22][23]. In many instances, Monte-Carlo simulations are then devised to account for the afore-mentioned phenomena [19,21,24,22].…”
Section: Introductionmentioning
confidence: 99%
“…(9), Weibull proposed that   should be replaced by the normal stresses acting on the material plane. The same kind of expression was introduced by Doudard [22] for a multiaxial fatigue model in order to take into account heat generated by local microplasticity induced by fatigue cycling. In the following, for sake of simplicity the parameter   0 y  will be considered to be negligible compared to the load level represented by a T .…”
Section: Meso-plasticity In the Matrix: Elastic Shakedown At The Mesomentioning
confidence: 99%
“…One observes that beyond a given stress level, that is closed to the fatigue limit, the steady-state temperature increase significantly (Figure 4). Recently, a two-scale probabilistic model has been proposed to identify HCF properties from self-heating measurement [6]. The influence on the fatigue properties of the studied steel can be determined by self-heating measurements by using specimen with a constant section that have been uniformerly pre-strained (figure 4).…”
Section: Introductionmentioning
confidence: 99%